சங்கப் பெண்மொழிக் கட்டமைப்பில் வினைச்சொற்கள் // Verbs in the Structural Framework of Sangam Women's Language - முனைவர் இர. ஹேமலதா / Dr. R. Hemalatha (Pandian Journal of Women's Studies)
Sangam literature has its distinct traditions and characteristics. In terms of its linguistic style, it is structured with a refined and firm structural framework. As Sangam Literature has emerged from a highly learned social backdrop, women were also capable of creating poetry with great skill at Sangam times. They expressed their inner and outer emotions through poetry. These poems were not mere empty verses but were deeply insightful works reflecting social concern and rooted in morality. The linguistic ability of these women was infinite. In terms of phonetics, vocabulary, syntax, the ideas conveyed and their authentic Tamil language is with excellence, coherence and beauty. The female poets of the Sangam era stood out for their skilful use of Tamil language. They handled verbs in both internal (personal) and external (social) contexts across the dimensions of texts, poets, themes and expressions using them both similarly and differently. This essay highlights the linguistic authority of the female poets of the Sangam period in particular to the use of their verbs.